Does probiotic consumption enhance wound healing? a systematic review - Togo, Camille (2022)
The use of probiotics is one of the emerging lines of treatment for wound healing. This systematic review aimed to summarize currently available evidence on the effect of oral or enteral probiotic therapy on skin or oral mucosal wound healing in humans. To verify the developments in this field and the level of available scientific evidence, we applied a broad search strategy with no restrictions on wound type, target population, probiotic strain, or intervention protocol used. This review included seven studies involving 348 individuals. Four studies reported positive outcomes for healing improvement after probiotic therapy, and none of the studies reported adverse effects or a marked increase in wound healing time. The positive or neutral results observed do not generate strong evidence regarding the effectiveness of probiotics for wound healing. However, they suggest a promising field for future clinical research where the probiotic strains used, type of wounds, and target population are controlled for.